Lemmus amurensis Vinogradov 1924 - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
30. Amur Brown Lemming Lemmus amurensis French: Lemming de 'Amour / German: AmurLemming / Spanish: Lemming del Amur Other common names: Amur Lemming Taxonomy. Lemmus amurensis Vinogradov, 1924, Pikan, on Zeya River, a tributary of Amur River, Siberia, Russia. Taxonomy and distribution of L. amurensis are not definitely known, and some consider it part of L. sibiricus. Others synonymize flavescens with sibiricus. Two subspecies recognized. Subspecies and Distribution. L.a.amurensisVinogradov,1924—fromETransbaikaliaandAmurRiverEalongthe SeaofOkhotskandacrossSchsofVerkhoyanskandCherskiyrangestoKolymaUpland(Russia). L. a. flavescens Vinogradov, 1925 — Kamchatka (Russia). Descriptive notes. Head-body 86-119 mm, tail 9-6-14-7 mm; weight 16-2-51 g. The Amur Brown Lemming is similar to the Siberian Brown Lemming (L. sibiricus) but is considerably smaller and has brighter pelage. Dorsum is brown, cheeks are rusty or yellow-buff, snoutis rusty, and gray venter is usually washed rusty or buffy. Dark medial stripe runs along back. Winter pelage is duller. Females have eight nipples. Skull is less ridged than that of the Siberian Brown Lemming, but interorbital crest is present in adults. No other peculiarities are evident. Molar pattern is essentially like in the Siberian Brown Lemming. Habitat. Marshes, mires, and bogs in larch (Larix, Pinaceae) or birch (Betula, Betulaceae) taiga, floodplains, and wet valleys ofrivers and brooks on mountain slopes at elevations of 300-1200 m. Vegetation cover is mosses; forbs; birch (B. exilis and B. middendorffi); shrubby cinquefoil (Dasiphorafruticosa) and spirea (Spiraea, both Rosaceae); Siberian alder (Alnus viridis fruticosa, Betulaceae); Siberian dwarf pine (Pinus pumila, Pinaceae); sedges (Carex) and sheathed cottonsedge (Eriophorum vaginatum, both Cyperceae); and Labrador tea (Ledum palustre), leatherleaf (Chamaedaphne calyculata), and bog bilberry (Vaccinium uliginosum, all Ericaceae). Amur Brown Lemmings occasionally occupy drier spots and rocky slopes but avoid dense coniferous ...